5b-3b-b=13

Simple and best practice solution for 5b-3b-b=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5b-3b-b=13 equation:


Simplifying
5b + -3b + -1b = 13

Combine like terms: 5b + -3b = 2b
2b + -1b = 13

Combine like terms: 2b + -1b = 1b
1b = 13

Solving
1b = 13

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Divide each side by '1'.
b = 13

Simplifying
b = 13

See similar equations:

| x^2-11x+15=2x+3 | | 4s-3s=9 | | x^2-11x+15= | | 10u-9u=17 | | 6w+12=20+2w | | 4p-3p+10+2p-4= | | 2X+(X-3)=-(X+1)+126 | | x^2+3x-17=2x-5 | | 3z-2z=16 | | BD=X+1+2X | | 18w-10w=16 | | 49-22x=4(9-5x)-3 | | 3x+2.5y=10000 | | -32=-7n-12 | | 2x^2-3t+4=0 | | f(x)=x^2-8+15 | | (X^2-64)(x^2-9)=0 | | (3h)2+(5h)4=46 | | 3x-9=2(x-7) | | -4w+13w+5=6w+31 | | 15t=-5t^2+20t | | -5i(3-4i)= | | x^2+4x+2=-12 | | 4x+2y-3x= | | 10=10+2f | | -2=8-e | | -9(4n-3)=23+8n | | 11x-101=-7x+169 | | (5-i)-(11-i)= | | Y=-200000*ln(500000000)+5000000 | | -32+8x=11x+25 | | 4x-5=3x-11 |

Equations solver categories